Effects of gymnastics activities on bone accrual during growth: A systematic review - Jürimäe, J.; Gruodyte-Raciene, R.; Baxter-Jones, A. D. G. (Journal of Sports Science & Medicine, 2018)
The amount of bone gained during childhood and adolescence impacts greatly on lifetime skeletal health. The purpose of this review is to summarize current evidence of the effects of gymnastics activities on bone mineral accrual during growth and to describe possible factors that influence bone mineral gains. The PubMed and SportDiscus databases were searched, and a total of 24 articles met the selection criteria and were included in this review. Artistic and rhythmic gymnasts presented higher bone mineral density and content values compared to untrained controls, despite possible negative effects associated with hormonal levels, dietary restrictions and body fat. The results suggest that gymnasts had similar bone turnover values compared to untrained controls. High-intensity mechanical loading of gymnastics activity appears to increase bone development and counterbalance negative effects, such as later pubertal development, lower body fat mass and lower hormone levels. In conclusion, gymnasts present higher bone mineral values in comparison with untrained controls. The osteogenic effect of gymnastics athletic activity has a positive influence on bone mineral accrual and overcomes the possible negative influence of high athletic activity that may cause negative energy balance and low body fat mass which are associated with lower bone accrual.